Wheat Yield Affected by Soil Temperature and Water under Mulching in Dryland. (1st November 2017) - He, Gang; Wang, Zhaohui; Ma, Xiaolong; He, Hongxia; Cao, Hanbing; Wang, Sen; Dai, Jian; Luo, Laichao; Huang, Ming; Malhi, Sukhdev S.
Abstract : Core Ideas: Plastic mulch increased soil temperature and water, thus increased wheat yield. High soil temperature by plastic mulch and planting legume reduced wheat yield. Incorporation of legume increased soil temperature of next wheat growing season. Planting legume increased soil water use in summer and decreased evapotranspiration in wheat season. In the Loess Plateau of northwestern China, soil water shortage is the main factor constraining dryland wheat ( Triticum aestivum L.) production. Soil mulching is considered an effective practice to improve wheat yield due to increased soil water storage, but the information related to integrated understanding of soil temperature and water is scarce. We conducted a location‐fixed field experiment with two soil mulching (plastic mulch and planting legume) treatments to confirm the effects of soil temperature and water on wheat yield under different precipitation levels. In 2014–2015 with higher than average precipitation, plastic mulch increased soil water storage by 13% at sowing and average soil temperature by 0.4°C, which in turn increased yield by 13%, compared to the control. In 2012–2013 with extremely lower than average precipitation, the high daily maximum soil temperature during wheat reproductive period decreased grain number per spike and grain weight by 16 and 4%, respectively, thus reduced yield by 16%. For planting legume, the lower soil water storage at sowing and high daily maximum soil temperature during the wheat reproductive period decreased the number of spikes per hectare and grain weight by 29 and 4%, respectively, resulting in a 37% decrease in yield in 2012–2013. In other years with relatively higher precipitation, the proper soil temperature and extra N input under planting legume alleviated the negative impact of yield decline. Overall, planting legume did not show any benefit for wheat yield, while plastic mulch provided an opportunity for increasing wheat yield in dryland.